The cognitive function of specialized languages: educational implications - OXBROW, GINA L.; LANKIEWICZ, HADRIAN A. (Glottodidactica, 2017)
The current article explores the problem of conceptualizing specialized languages in the general body of language, and, as such, will refer extensively to the concepts described by S. Grucza (2013) based on the anthropocentric theory of language per se. By focusing on the cognitive function of specialized languages and evoking the principles of ecological linguistics, the necessity of integrating specialized knowledge with specialized language will be highlighted. Consequently, pedagogical implications for ESP syllabi and teacher education will be drawn.